STUDI LITERATUR MODEL PROJECT BASED LEARNING (PJBL) TERHADAP HASIL BELAJAR MATEMATIKA DI SD - Dini Meilia Putri; Melva Zainil; Inggria Kharisma; Annisa Olivia Memosa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Mathematics learning in elementary school plays an important role in developing students’ logical, critical, and systematic thinking skills. However, in practice, mathematics learning in the classroom is still often carried out using conventional learning methods that are teacher-centered. This condition causes students to be less active in the learning process and easily feel bored, which ultimately affects their learning outcomes. Therefore, it is necessary to apply a learning model that can increase students' participation and involvement in learning activities. One of the learning models that can be applied is Project Based Learning (PjBL). This study aims to describe the application of the Project Based Learning model towards mathematics learning outcomes of elementary school students. The method used in this research is a literature study (library research) by reviewing various sources such as books, scientific journals, and previous research related to the topic. The data used in this study were obtained from ten journal articles discussing the implementation of Project Based Learning in mathematics learning at the elementary school level. The results of the literature review indicate that the implementation of the Project Based Learning model can improve students’ mathematics learning outcomes. In addition, this learning model is also able to increase students’ learning motivation, collaboration skills, and critical thinking abilities during the learning process. Therefore, Project Based Learning can be used as an effective learning model to improve mathematics learning outcomes in elementary schools. Keywords: Project Based Learning (PjBL), learning outcomes, mathematics.